Vacuum Stability in Supersymmetric Reduced Minimal 3-3-1 Model - Thao, Nguyen Huy; Phuong, Ly Thi Mai; Hue, Le Tho (Communications in Physics, 2013)
We investigate the vacuum stability conditions of theSupersymmetric reduced minimal 331 model (SUSYRM331) that createimportant consequences on Higgs mass spectrum as well assoft-parameters of the model. We prove that if this condition issatisfied then all Higgses are massive. Furthermore,soft-parameters should be in order of \(SU(3)_L\) scale. Based onthis, we investigate in detail masses of CP-even neutral anddoubly charged Higgses in the model. The neutral Higgs sectorincludes one light Higgs with mass at tree level \(m_{H^0_1}\simeq m_Z|\cos 2γ | < 92.0\) GeV and three other heavy Higgses. Fordoubly charged Higgses, there may exist a light Higgs which can beobserved by recent colliders such as LHC.